(untitled) (Global Journals of Research in Engineering, 2023)
This study aims to investigate the influence of a number of related parameters namely temperature pressure flow rate and pH on the corrosion penetration rate CPR of crude oil transportation process by pipelines It intends the mathematical model of these parameters as independent variables with corrosion penetration rate as a dependent variable The model was used to establish the best values of these parameters using the response surface methodology Aspen HYSYS software was utilized to simulate the experiments and to calculate the corrosion penetration rate for each experiment The experiments designed based on the central composite experimental design CCD using Minitab 17 software The mean absolute percentage error was used to determine the conformance of the developed mathematical model Its value was 0 02 this indicates that the developed mathematical model was consistent The Nash Sutcliffe efficiency NSE was also calculated Its value was 0 999 which confirms the high-efficiency of the model The optimal corrosion penetration rate conditions were determined temperature 100 F pressure 360 psig flow rate 150 000 bbl day and pH 5 65 Accordingly the minimum corrosion penetration rate is 3 98 mm year